A constant phase stable over the wideband for beam steering antenna applications. Issue 12 (21st September 2022) - Wang, Enlin; Yan, Zehong
Abstract: A K‐band wideband self‐compensating phase shifter based on gap waveguide is presented. The traditional waveguide phase shifter cannot easily achieve a stable phase shift over wideband due to the dispersion effect. Accordingly, a short‐circuit structure and a slow‐wave structure are designed in this paper, and their phase shifts show a positive‐slope and a reverse‐slope with respect to frequency. The two structures are realized using the tuning screw technology, and different phase shifts of 0–140° are realized by adjusting the number of screws. Besides, two structures are combined with a high‐isolation power divider to realize a phase shifter with high phase and amplitude stability. The phase shifter is manufactured and measurement results of the eight phase shifts of the phase shifter show that the bandwidth of the phase changes within ±5° was greater than 30%. Finally, a four‐way feeding network has been designed, which is used to form a four‐element linear array. Generally, when the antenna beam is steered, the main‐beam directions of different frequencies are not consistent. Therefore, by compensating the slope of the phase shifter with respect to the frequency, an array antenna whose main‐beam direction does not change with respect to frequency is designed.